Assessing the temporal dynamics of aquatic and terrestrial litter decomposition in an alpine forest. (1st June 2018) - Yue, Kai; García‐Palacios, Pablo; Parsons, Scott A.; Yang, Wanqin; Peng, Yan; Tan, Bo; Huang, Chunping; Wu, Fuzhong
Abstract: Litter decomposition supplies nutrients and energy within and among aquatic and terrestrial ecosystems. It is driven by several biotic and abiotic factors, the relative importance of which may change during litter decay. However, to date, very few studies have addressed the temporal dynamics of such factors across aquatic and terrestrial ecosystems, which limits our understanding of litter decomposition process. To assess the temporal dynamics of major abiotic and biotic litter decomposition drivers, we conducted a 2‐year field experiment to evaluate the losses of foliar litter carbon (C) and nitrogen (N) in alpine streams, riparian zones and forest floors. Environmental (soil, water and climatic) factors were continuously monitored, and incubated plant litter was sampled over time to assess temporal changes in litter chemistry and microbial diversity. We analysed sequential litter decomposition stages based on mass‐loss intervals and used structural equation modelling to disentangle the relative importance of each biotic and abiotic driver. Our results suggested that across the aquatic and terrestrial ecosystems, litter C and N loss was generally controlled by a common hierarchy of drivers: (a) Environment and initial litter quality regulated C and N loss via both direct and indirect effects, and their total effects were mainly significant in the early and late decomposition stages, respectively; (b) changes in litter chemistry significantly influenced litter decomposition throughout the decomposition process, mainly via direct effects; and (c) microbial diversity per se showed minimal effects on litter C and N loss. The identified common hierarchy of biotic and abiotic drivers and their direct and indirect effects on C and N loss at different decomposition stages across aquatic and terrestrial ecosystems indicates the possibility of integrating aquatic and terrestrial decomposition into a single framework for future construction of models accounting for temporal dynamics of litter decomposition. A plain language summary is available for this article. Abstract : Plain Language Summary